THE RELATIONSHIP BETWEEN WORK SHIFT SYSTEM AND WORK STRESS ON EMPLOYEE PERFORMANCE IN INDONESIA: A LITERATURE REVIEW - Indah Purwitasari; Endang Dwiyanti (Journal of Community Mental Health and Public Policy, 2026)
Background: The implementation of shift work systems across various industrial sectors in Indonesia has increased to support 24-hour operations. However, shift work may increase work-related stress and negatively affect employee performance. Previous studies have reported varied findings depending on sector and job characteristics. Purpose: This study aims to analyze the relationship between shift work systems and work stress on employee performance in Indonesia. Method: This study employed a systematic literature review method, with data sources obtained from Google Scholar, Garuda, ResearchGate, and Semantic Scholar. A total of six articles were selected based on predetermined inclusion and exclusion criteria. Results: Shift work systems and work stress are associated with employee performance, both partially and simultaneously. Work stress has a direct relationship with performance, while shift work is indirectly related through increased stress. In the manufacturing sector, work stress is more dominant, whereas in the healthcare sector, the relationship of shift work is stronger. In the modern retail sector, the relationship of both variables varies depending on work management practices. Conclusion: In general, shift work systems are associated with employee performance through increased work stress. Therefore, effective shift system management and the implementation of stress management are important factors in maintaining employee performance. Abstrak Latar Belakang: Penerapan sistem shift kerja di berbagai sektor industri Indonesia semakin meningkat untuk mendukung operasional 24 jam. Namun, berpotensi meningkatkan stres kerja yang berdampak pada kinerja karyawan. Hasil penelitian sebelumnya menunjukkan bahwa hubungan tersebut bervariasi antar sektor industri dan karakteristik pekerjaan. Tujuan: untuk menganalisis hubungan sistem shift kerja dan stres kerja terhadap kinerja karyawan di Indonesia. Metode: Menggunakan metode tinjauan literatur sistematis, dengan sumber data dari Google Scholar, Garuda, ResearchGate, dan Semantic Scholar. Sebanyak 6 artikel dipilih berdasarkan kriteria inklusi dan eksklusi yang telah ditentukan. Hasil: Sistem shift kerja dan stres kerja berhubungan dengan kinerja karyawan, baik secara parsial maupun simultan. Stres kerja terbukti berhubungan langsung terhadap kinerja. Sementara itu, hubungan shift kerja terjadi secara tidak langsung melalui peningkatan stres. Pada sektor manufaktur, stres kerja lebih dominan, sedangkan pada sektor kesehatan hubungan shift kerja lebih kuat. Pada sektor ritel modern, hubungan keduanya bervariasi tergantung pengelolaan kerja. Kesimpulan: Secara umum, sistem shift kerja berhubungan dengan kinerja karyawan melalui peningkatan stres kerja. Oleh karena itu, pengelolaan sistem shift dan penerapan manajemen stres menjadi faktor penting dalam menjaga kinerja karyawan.